Determinants of Preterm Labour in a Rural Medical College Hospital in Western Maharashtra - Shubhada, Sunil Avachat; Kambale, SV; Phalke, BD (Nepal Journal of Obstetrics and Gynaecology, 2013)
Aims: This study was done to estimate the incidence of preterm labour and to study the causes of preterm labour in a teaching hospital. Methods: A cross sectional study was conducted in a medical college hospital in rural area among all patients who delivered during study period. Data was collected by interview technique and analyzed by appropriate statistical methods. Results: Total 2105 deliveries occurred during study period and the incidence of preterm delivery in the study was 15%. Incidence of preterm labour was comparatively more among multigravida (49.5%). Out of 315 preterm labour cases, 234 (74.25%) were from low socioeconomic status. Forty-one percent preterm labors were idiopathic, 17% cases had maternal- fetal complications and 15% cases had recurrent urinary tract infections. Significant association was observed between previous history of preterm labour and current preterm labour after applying Z test. Conclusions: Incidence of preterm labour was 15% among the hospital deliveries in a teaching hospital in rural area. Preterm labour was more common among women of low socioeconomic status, among multigravida and among women having previous history of preterm labour. Nepal Journal of Obstetrics and Gynaecology / Vol 8 / No. 1 / Issue 15 / Jan- June, 2013 / 31-33 DOI: http://dx.doi.org/10.3126/njog.v8i1.8858